Laparoscopic adrenalectomy for large adrenal pheochromocytoma: a case report and discussion - Prakash, Shwetank; Thakare, Vaibhav; Goel, Anubhav; Mohan, Atiharsh (International Surgery Journal, 2017)
A 40-year-old patient who presented hypertension and hyperglyemia, on CECT showing 7x6.2x5 cm sized retroperitoneal mass lesion in left para-aortic region extending to suprarenal region, diagnosed as pheochromocytoma. Patients BP monitored hourly, started antihypertensive and insulin. After adequate control of blood pressure and blood sugar patient planned for laparoscopic adrenalectomy by lateral transperitoneal approach. GA and combined epidural spinal anesthesia given. The patient was placed in the right-lateral decubitus position with the left side up. The surgeon and assistant stand on the right side of the table. and 4 trocars were inserted. The first port is situated 2 cm below the costal margin at the midclavicular line. The lateral port is placed under direct visualization at the anterior axillary line. The remaining port was placed between the two port. Adrenal Vein bluntly dissected, the vein is carefully doubly ligated with hemlock clips and transacted between clips. The adrenal gland was retracted in a superolateral direction and the harmonic scalpel was used to continue dissection laterally. The specimen was retrieved via a small, 4 cm incision on lateral costal margin. Histopathology of tumor specimen confirmed diagnosis as pheochromocytoma. Laparoscopy offers a better anatomical exposure, shorter length of stay, a decrease in postoperative pain, faster return to preoperative activity level, improved cosmesis, and reduced blood loss, early to resumption of oral feeding.